Terang Bulan Dance in Karo Society Aesthetic Analysis - Ruth Hertami Dyah Nugrahaningsih; Dilinar Adlin; Inggit Prastiawan (Budapest International Research and Critics University, 2020)
Terang Bulan dance is one of the regional creations which is traditionally used by the Karo people in North Sumatra Province. The title of the dance follows the title of the song used as a dance accompaniment song. This dance presents a dramatic effect through the form and variety of movements that are in harmony with the accompanying song. The explanation of the aesthetic value contained in this dance is based on the concept and technique of movement or how to perform the movements which are divided into four parts. The whole movement expresses the aesthetic value content that is manifested in caution, calmness, which emphasizes courtesy in every move.